Meningkatkan Kreativitas Belajar PAKBP dengan Model PBL pada Materi Manusia Diciptakan Secitra dengan Allah Fase C Kelas 5 SDN Begalon 1 Surakarta - Ade Mardiana; Wuriningsih FR; Budi Hartana (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Creativity is one of the dimensions in the Pancasila Student Profile. Creative students can produce original ideas, create original work and actions, and have flexibility in thinking to find alternative solutions to problems. This research is of the type Classroom Action Research. To increase students' learning creativity with the Problem-Based Learning model on human material created as an image of God in Catholic Religious Education and Character Education subjects. The subjects of this research were students at SDN Begalon 1 Surakarta City for the 2024/2025 Academic Year Phase C Class V. Data collection techniques are carried out using observation, initial tests, formative tests, and documentation. The results of this research are: 1) The application of the stages in PBL has an impact on students' ability to solve a problem creatively; 2) The average P3 Qualitative Score is from 72 to 86, in the proficient category; 3) The average cognitive score in cycle I was 80 to 88 in cycle II, in the advanced category.